UTILIZING MEMES TO PROMOTE STUDENTS’ MOTIVATION IN LANGUAGE CLASSROOM - Purnama, Agnes Dian; Desiarti, Elsa Marina; Aflahah, Noor Aida; Ekaningrum, Vindy Cahya (LET: Linguistics, Literature and English Teaching Journal, 2017)
Keeping students? motivation to learn L2 is a challenging activity in teaching and learning process. Teachers are expected to perform their job dutifully by engaging students into attractive learning activities. At the same time, they are also contested with students? characteristics diversity. The utilization of memes is a proposed teaching strategy to minimize the gap between students? traits, technology rapid development, and the constant need of renewing effort to enhance students? performance. Seeking an opportunity of integrating between various mobile application, gadgets as well as internet access, memes creation may be considered as a breakthrough in educational field. The result of this study shows students? positive responses in creating memes activity. Most of the EFL students? responses stated that the activity is interesting therefore it is able to boost their motivation. The activity covers up three essential motivation values for learning an L2; intrinsic value, integrative value, and instrumental value.